2016
DOI: 10.14202/vetworld.2016.203-206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of motion and kinematic characteristics of frozen-thawed Sirohi goat semen using computer-assisted semen analysis

Abstract: Aim:The aim was to determine the motion and kinematics characteristic of frozen-thawed spermatozoa in Sirohi goat using computer-assisted semen analysis. Materials and Methods:A study was carried out in Sirohi buck. Semen collection was made biweekly from each buck with the help of artificial vagina. A total of 12 ejaculates were collected from two bucks (six ejaculates from each buck). Freshly collected semen was pooled and later evaluated. The pooled semen sample was extended with standard glycerolated egg y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…The total and progressive motility of fresh spermatozoa from Black Bengal goats reported by Islam et al, 29 were found similar with the current investigation. The motility found drastically decreased at cryopreservation of buck spermatozoa along with seminal plasma, 2,41‐43 which has also been found in the current investigation. It has been reported that buck seminal plasma protein BUSgp60 interacts with contents of semen extender especially egg yolk and skim milk, which are responsible for morphological damage and reduced motility 12,13,16,44 .…”
Section: Discussionsupporting
confidence: 88%
“…The total and progressive motility of fresh spermatozoa from Black Bengal goats reported by Islam et al, 29 were found similar with the current investigation. The motility found drastically decreased at cryopreservation of buck spermatozoa along with seminal plasma, 2,41‐43 which has also been found in the current investigation. It has been reported that buck seminal plasma protein BUSgp60 interacts with contents of semen extender especially egg yolk and skim milk, which are responsible for morphological damage and reduced motility 12,13,16,44 .…”
Section: Discussionsupporting
confidence: 88%
“…The Biovis CASA based results of fresh diluted and postthaw motility rating for Gir and Murrah bull sperm particularly in control TFYG extender were in accordance with the recent observations of Pathak et al (2019 a,b ; 2020) using the same Biovis CASA version and also with Karthikeya (2003), Kathiravan et al (2008), Patel et al (2012) and Patel and Fortification of Tris Extender with Mifepristone, Sericin and Taurine Improves Velocity and Kinematics of Fresh and... (2016) with different versions of CASA. The present findings on kind of sperm motility ratings for fresh diluted and/or frozen-thawed semen observed also concurred with the earlier reports on different farm animals species by various workers using different grades of CASA machines and chambers (Anderson et al, 1992;Tardif et al, 1997;Abbas et al, 2001;Rasul et al, 2001;Mandal et al, 2003;Hoflack et al, 2007;Anand and Yadav, 2016;Rodriguez-Montana and Roa-Guerrero, 2017). Although Kumar et al (2018) using same version of Biovis CASA, found much lower values of motility rating for buffalo sperm in fresh diluted, equilibrated and frozen-thawed semen than the present findings in either of the species studied.…”
Section: )supporting
confidence: 92%
“…Nevertheless, using an objective approach can be more accurate, avoiding the high variability among experimental units or evaluators for the seminal parameters (Verstegen et al, 2002). However, the sperm motility verified in our data was similar to that described with an objective protocol for seminal analysis of fresh and frozenthawed buck semen using a computer-assisted semen analysis (CASA) system (Jiménez-Rabadán et al, 2012;Anand and Yadav, 2016;Falchi et al, 2020). Therefore, these findings indicated that the seminal characteristics observed in our data did not differ to those described.…”
Section: Discussionsupporting
confidence: 76%